Efektivitas Media Visual dalm Meningkatkan Pengetahuan tentang Seribu Hari Pertama Kehidupan Remaja Putri: The Effectiveness of Audio Visual Media in Increasing Knowledge About the First Thousand Days of Life Young Women - Sunaeni Sunaeni; Inayah M Abduh; Mariana Isir (Jurnal Surya Medika (JSM), 2023)
Background: Understanding nutrition in the first thousand days of human life needs to be promoted in preventing stunting. Adolescent girls have a key role in maintaining health during pregnancy, of which 28.72% of women in West Papua aged 15-19 years (SMP-SMA) are pregnant for the first time. Audio-visual media can be used as an alternative in disseminating information on stunting prevention during the "golden period". Methods: The research methodaapproach usesquasi-experimental pre- and post-test design. The population is 468 female students. The sampling technique used simple random sampling to get 46 respondents. The data collection instrument used a questionnaire with 34 questions. Data collection was carried out directly on young women before and after being given treatment in the form of counseling using audiovisual. Data analysis used paired T Test with the help of software at a significance level of 0.05 and presented in the table Results: The results showed p value 0.001, there was a significant difference in knowledge about the first thousand days of life for young women at MAN Model Sorong before and after being given treatment. Conclusion: Counseling about the first thousand days of life is very important for all young women, cross-sectoral collaboration is needed to produce the next generation that is free from stunting.